Peningkatan Hasil Belajar Matematika materi Pengukuran Sudut Melalui Model Pembelajaran Problem Based Learning (PBL) di Kelas IV SDN Bandung Tahun Ajaran 2020/2021 - Pulung Ardiyanto; Wahyudi Wahyudi; Suhartono Suhartono (Universitas Sebelas Maret, 2022)
AbstractLearning outcomes are crucial as the indication if learning process is succeed or failure. The study aimed to improve the mathematics learning outcomes about Angle Measurement through the Problem Based Learning (PBL). It was collaborative classroom action research (CAR) conducted in three cycles. The subjects were teachers and 18 fourth grade students of SDN Bandung. Data collection techniques used non-test techniques including observation, interviews, documents, and test. The data validity used triangulation of techniques and triangulation of sources. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results indicated that the students’ mathematics learning outcomes increased after applying Problem Based Learning (PBL). It concludes that the application of Problem Based Learning (PBL) improves the mathematics learning outcomes about angle measurement.